2021
DOI: 10.1101/2021.08.03.454940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Level of Interaction between Phages and Bacteria in an Artisanal Raw Milk Cheese Microbial Community

Abstract: Endogenous starter cultures are used in the production of several cheeses around the world, such as Parmigiano Reggiano, in Italy, Epoisses, in France, and Canastra, in Brazil. These microbial communities are responsible for many of the intrinsic characteristics of each of these cheeses. Bacteriophages are ubiquitous around the world, well known to be involved in the modulation of complex microbiological processes. However, little is known about phage bacteria growth dynamics in cheese production systems, wher… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…: Jacobs-Sera et al, 2020;Klyczek et al, 2017;de Melo et al, 2020) or Swiss-type cheese (Propionibacterium: Cheng et al, 2018) are also known and, in some cases might be responsible of defects in cheese. More recently, metavirome studies are being carried out in starter cultures and in cheeses (Colombo et al, 2018;Dugat-Bony et al, 2020;Frantzen and Holo, 2019;Muhammed et al, 2017;Queiroz et al, 2021) and are allowing the discovery of novel bacteriophage-host interactions relevant to cheese ecology and quality.…”
Section: Phage-bacteria Interaction Networkmentioning
confidence: 99%
“…: Jacobs-Sera et al, 2020;Klyczek et al, 2017;de Melo et al, 2020) or Swiss-type cheese (Propionibacterium: Cheng et al, 2018) are also known and, in some cases might be responsible of defects in cheese. More recently, metavirome studies are being carried out in starter cultures and in cheeses (Colombo et al, 2018;Dugat-Bony et al, 2020;Frantzen and Holo, 2019;Muhammed et al, 2017;Queiroz et al, 2021) and are allowing the discovery of novel bacteriophage-host interactions relevant to cheese ecology and quality.…”
Section: Phage-bacteria Interaction Networkmentioning
confidence: 99%
“…It has been observed that some viruses can positively influence the fermentation process of fermented foods [ 5 ]. Reports showed that, in some fermented food such as cocoa beans and milk cheese, viruses can regulate bacterial community succession during fermentation, and might have beneficial effects on the quality and sensory characteristics of fermented products [ 6 , 7 ]. Moreover, Pacini and Ruggiero [ 8 ] suggested that phages have potential probiotic properties in modern fermented foods and fermented milk supplemented with probiotics bacteriophage can improve the efficacy of probiotics in food.…”
Section: Introductionmentioning
confidence: 99%